Emergence, Growth and Role of Think Tanks in Nepal - Raut, Sunita (Bagiswori Journal, 2019)
The term think tank defines the independent institute engaging in research, policy advocacy, advisor of policy maker, informing and sensitizing the public debate related to policy issues. This article is an attempt to analyze the emergence, growth and role of think tanks in Nepal. It looks at the background, evolution and role of think tanks from history and present, to understand the broad pattern of political and social development process that conditions their role in this context. This paper also examines the gap between knowledge-power interfaces and suggest to site reflecting the knowledge-power nexus borne out of the complex interplay between endogenous and exogenous political process. It discusses the issues based on data and information gathered through the secondary sources of information which have been used to sharpen the conceptual issues related to this study.